2005
DOI: 10.1007/s10705-004-7352-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of N2O and CH4 Emission from Rice and Wheat Cropping Systems Using Dicyandiamide and Hydroquinone

Abstract: Agriculture contributes considerably to the emission of greenhouse gases, such as N 2 O and CH 4 . Here we summarize results from previous pot experiments assessing the effectiveness of urease and nitrification inhibitors reducing both N 2 O and CH 4 emissions from wheat and rice cropping systems fertilized with urea (U). For the wheat cropping system, using a cambisol, we observed that the application of U with hydroquinone (HQ, a urease inhibitor), U with dicyandiamide (DCD, a nitrification inhibitor) and U … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 36 publications
(34 reference statements)
8
17
2
1
Order By: Relevance
“…A two-way ANOVA indicated that seasonal N 2 O emissions during the vegetable-growing periods were significantly affected by nitrapyrin application (Table 4, p < 0.001), in agreement with previous results (Ma et al, 2013;Xiong et al, 2013;Zhang et al, 2015). Different types of NI that were effective in reducing N 2 O have been reported by previous studies (Xu et al, 2000;Boeckx et al, 2005;Zaman et al, 2008Zaman et al, , 2009; Zaman and Blenner- DF -degrees of freedom; SS -sum of squares; F -ratio of mean squares of two independent samples; P -index of differences between the control group and the experimental group. If p < 0.05 and p < 0.001, significant differences exists between the control group and the experimental group.…”
Section: Effects Of Nitrapyrin As Nitrification Inhibitor On N 2 O Emsupporting
confidence: 90%
“…A two-way ANOVA indicated that seasonal N 2 O emissions during the vegetable-growing periods were significantly affected by nitrapyrin application (Table 4, p < 0.001), in agreement with previous results (Ma et al, 2013;Xiong et al, 2013;Zhang et al, 2015). Different types of NI that were effective in reducing N 2 O have been reported by previous studies (Xu et al, 2000;Boeckx et al, 2005;Zaman et al, 2008Zaman et al, , 2009; Zaman and Blenner- DF -degrees of freedom; SS -sum of squares; F -ratio of mean squares of two independent samples; P -index of differences between the control group and the experimental group. If p < 0.05 and p < 0.001, significant differences exists between the control group and the experimental group.…”
Section: Effects Of Nitrapyrin As Nitrification Inhibitor On N 2 O Emsupporting
confidence: 90%
“…Maintaining a high soil NH 4 + content for a longer time by regulating the rapid conversion of soil N can effectively alleviate NO 3 À accumulation and leaching losses, in addition to reducing N 2 O emissions Fangueiro et al, 2009). Thus, a large number of studies have shown that N fertilizers with NIs are more environmentally friendly (Xu et al, 2000;Boeckx et al, 2005;Zaman et al, 2008Zaman et al, , 2009Zaman and Blennerhassett, 2010;Ding et al, 2011). In the present study, we observed that the application of CP and BNI increased soil NH 4 + content and slightly decreased soil NO 3 À content.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, we concluded that N 2 O emissions from mesocosms with earthworms (E. fetida) were mitigated by NI application. Our results confirm that the application of NI can enhance N fertilizer efficiency, by decreasing N 2 O emission from soil, which may mean that the agriculture use of NI is likely to increase in the future (Fettweis et al 2001;Boeckx et al 2005;Li et al 2009;Merino et al 2001). However, only one species of earthworm (E. fetida) was applied in this study, and future research is needed to confirm these results under field conditions and with different species of earthworms.…”
Section: Discussionsupporting
confidence: 82%
“…arable land and grassland, by inhibiting the nitrifying activities of ammonia-oxidizing bacteria in soil (Fettweis et al 2001;Boeckx et al 2005;Li et al 2009). Dicyandiamide (DCD) reduced N 2 O emissions from maize soil by 37 % (Zaman et al 2008) and that 3,4-dimethylpyrazole phosphate (DMPP) reduced N 2 O emissions by 49 % (Azam et al 2001).…”
Section: Introductionmentioning
confidence: 99%